LEGAL PHILOSOPHY REVIEW: THE PARTICIPATORY PARADIGM FOR VIOLENCE AGAINST WOMEN IN CENTRAL JAVA - Cahya Wulandari (Yustisia Jurnal Hukum, 2020)
This article will analyze the participatory paradigm for the empowerment problem of women of the village violence victims in central Java based on three questions in the form of ontology, epistemology, and methodology. Community involvement began when identifying problems to formulate joint actions, while the research results were directly applied to the problems encountered. Victims of violence in women are considered to be very understanding of the problems faced so that they are expected to be found the right solution to be applied in the community and provide results under expectations. In the process of Participatory Action Research (PAR) There is a process of digging, seeking, investigating issues and problems of women in the issue of women's trafficking, sexual exploitation in a collaborative research/collaboration. Research is done in an equal relationship which then ends up doing the action together. Related to the issue of violence against women raises participation and raises women's power to build a good relationship between victims of violence against women, between women and the wider community, and among women victims of violence with researchers.